Pengaruh Waktu Pemangkasan Pucuk dan Konsentrasi Pupuk Organik Cair (POC) Limbah Air Lele terhadap Pertumbuhan dan Hasil Tanaman Mentimun Baby (Cucumis sativus L.) - Pratiwi, Pipin Ana; Sasmita, Ellen Rosyelina (Program Studi Agroteknologi INSTIPER, 2025)
Cucumber is vegetable containing protein, fat, and vitamins. One way to increase growth and yield cucumbers by pruning shoots and catfish water LOF. Study aims to determine best time for pruning shoots and concentration catfish water LOF the growth and yield cucumbers. Study design Completely Randomized Design (CRD) Factorial consisting two factors and one control. First factor time pruning shoots 3 levels, namely: pruning shoots aged 14, 21, and 28 HST. Second factor concentration catfish water POC 3 levels, namely: concentrations 200 ml/L, 300 ml/L, and 400 ml/L. Control is without pruning and catfish water. Results analyzed ANOVA, to find out real difference between treatments, followed by Duncan Multiple Range Test (DMRT) 5% level. Testing treatment with control using Ortogonal Contrast. The results showed there was an interaction between treatment pruning shoots and concentration catfish water LOF, parameters of plant length 14 DAP, stem diameter 21 DAP, number female flowers 35 DAP, weight a fruit and a plant. Pruning treatment 28 DAP showed the best results for number leaves 14 DAP. Treatment catfish water concentration 300 ml/L showed best results for parameters number of leaves 14 DAP, leaf area, and leaf area index.